2021
DOI: 10.3390/bs11050065
|View full text |Cite
|
Sign up to set email alerts
|

Food Neophobia and Food Disgust: The Mediating Role of Perceived Vulnerability to Disease

Abstract: Negative attitudes towards food are influenced by two factors, neophobia and often related disgust. Neophobia is the tendency to avoid new foods, while food disgust is the refusal of food that is considered potentially harmful to health. The study presented here aims to analyze the correlation between these two attitudes and the possible mediation operated by the perception of vulnerability to diseases, in order to understand if and how this contributes to the disgust towards certain unfamiliar foods. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…This can be explained as Perceived Infectability is a cognitive factor about fears, beliefs, and subjective perceptions, whereas Germ Aversion is more related to disgust or discomfort about certain risk behaviors (Díaz et al, 2016). Our findings are also supported by the studies developed by Santisi et al (2021), who observed positive and significant relationships between a disgust scale and Perceived Infectability, and by the study of , who found positive and significant relationships between physical disgust and germ aversion.…”
Section: Discussionsupporting
confidence: 83%
“…This can be explained as Perceived Infectability is a cognitive factor about fears, beliefs, and subjective perceptions, whereas Germ Aversion is more related to disgust or discomfort about certain risk behaviors (Díaz et al, 2016). Our findings are also supported by the studies developed by Santisi et al (2021), who observed positive and significant relationships between a disgust scale and Perceived Infectability, and by the study of , who found positive and significant relationships between physical disgust and germ aversion.…”
Section: Discussionsupporting
confidence: 83%
“…However, in the present study, apart from neophobic potential, another important characteristic that prevented food neophobic individuals from choosing a dish was the presence of animal-based ingredients. Animal-based components may be associated with the avoidance of a product by food neophobic individuals, as it may be related to food disgust due to a high risk of the transmission of toxins and pathogens, as well as a need to protect social order and follow moral principles [ 44 ]. Numerous studies have shown that food neophobia was associated with the reduced consumption or pleasure from the consumption of meat and offal [ 14 , 45 , 46 ], as well as fish and shellfish [ 14 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be indicated that familiarity with a specific cuisine may change the food choices within a restaurant menu. For starters and desserts, familiarity with French cuisine encouraged respondents to choose dishes containing animal-based components, which may be associated with reduced disgust [ 44 ]. However, a reverse association was observed for soups, which may have resulted from the description of an animal-based soup with non-neophobic potential, namely consommé, as a meat and vegetable broth.…”
Section: Discussionmentioning
confidence: 99%
“…There is a constant pull between consumers’ state of neophilia and neophobia usually referred to as the “omnivore's dilemma” (Henchion et al., 2016). While the former is largely due to their quest for novelty and variety in their diet for pleasure, nutrition, and health, the latter is usually associated with food disgust and it is a behavioral tendency that protects humans from ingesting toxin and other pathogens (Al‐Shawaf et al., 2015; Santisi et al., 2021). Human food neophobia, which has been found to be much stronger toward animal‐derived foods, may also be contributed to by consumers’ social variables (including; religion, culture, socio‐economic status, values, beliefs, etc.)…”
Section: Challenges In the Utilization Of The Fifth Quartermentioning
confidence: 99%
“…and some unpleasant sensory attributes of the food. While several factors have been suggested to contribute to these conflicting motives, the extra layer added by the more recent consumer concerns about the environment may play a significant role in their willingness to further explore products/ingredients from the fifth quarter in their diet among other avenues knowing that their actions ultimately contribute toward environmental sustainability objectives (Santisi et al, 2021). Henchion et al (2016) have further shown that if danger is perceived by consumers, the food will be rejected irrespective of the benefits inherent, whereas, if safety is assured, then taste becomes critical.…”
Section: Consumer Acceptance Factorsmentioning
confidence: 99%